Pengaruh Struktur Modal, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2014-2018 - Gusmiarni; Delviana Manalu, Theresia (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To determine the effect of capital structure, profitability and company size on firm value in manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange. Background Problems: The larger the company, the greater the funds needed for the company's operational activities with sources of funds coming from external parties which will affect the company's obligations with greater dependents. Novelty: Retesting on different industries, test periods and test equipment. Research Methods: The research sample consisted of 20 companies in various sectors of the manufacturing industry with the method used, namely purposive sampling, with an analysis tool, Eviews. Finding/Results: That capital structure has a negative and significant effect on firm value, profitability has a negative and significant effect on firm value, and firm size has a negative but not significant effect on firm value. Conclusion: In company policy, it is better to use own capital funds to finance the company's operational costs, not from debt.